2020
DOI: 10.1007/s00264-020-04769-6
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged social lockdown during COVID-19 pandemic and hip fracture epidemiology

Abstract: Purpose To analyse the impact of prolonged mandatory lockdown due to COVID-19 on hip fracture epidemiology. Methods Retrospective case-control study of 160 hip fractures operated upon between December 2019 and May 2020. Based on the date of declaration of national lockdown, the cohort was separated into two groups: 'pre-COVID time' (PCT), including 86 patients, and 'COVID time' (CT), consisting of 74 patients. All CT patients tested negative for SARS-CoV-2. Patients were stratified based on demographic charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
68
2
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(82 citation statements)
references
References 34 publications
6
68
2
5
Order By: Relevance
“…A total of 45 studies were retrieved after the search of electronic databases using the keywords; of which, eight studies were eligible for review after screening[ 9 , 19 , 20 , 27 - 29 , 38 , 39 ] (Figure 1 ). There were three prospective studies and five retrospective comparative studies.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A total of 45 studies were retrieved after the search of electronic databases using the keywords; of which, eight studies were eligible for review after screening[ 9 , 19 , 20 , 27 - 29 , 38 , 39 ] (Figure 1 ). There were three prospective studies and five retrospective comparative studies.…”
Section: Resultsmentioning
confidence: 99%
“…The preoperative morbidity status of the patients in both pandemic and pre-pandemic periods were compared using the American Society of Anesthesiologists (ASA) classification. Pooled analysis of five studies ( n = 1159) revealed significantly increased number of severely morbid (ASA grade > 3) hip fracture patients who were treated during the pandemic period (OR, 1.43; 95%CI, 1.08, 1.89; P = 0.01)[ 9 , 27 , 29 , 38 , 39 ]. Egol et al [ 20 ] (2020) did not observe a significant difference in preoperative morbidity using the Charlson Co-morbidity index between 2020 hip fracture cohort and 2019 hip fracture cohort.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations